(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: This article explores the ecology of aquatic plants and their role in aquatic ecosystems. It discusses various types of aquatic plants and their ecological management. The article also examines the impact of climate change on aquatic plants and water bodies. Аннотация: Эта статья исследует экологию водных растений и их роль в водных экосистемах. Рассматриваются различные виды водных растений и их экологическое управление. Также в статье обсуждается влияние изменения климата на водные растения и водоемы.